2022
DOI: 10.1080/22221751.2022.2069515
|View full text |Cite
|
Sign up to set email alerts
|

Assessing potential pathogenicity of novel highly pathogenic avian influenza (H5N6) viruses isolated from Mongolian wild duck feces using a mouse model

Abstract: Several novel highly pathogenic avian influenza (HPAIVs) A(H5N6) viruses were reported in Mongolia in 2020, some of which included host-specific markers associated with mammalian infection. However, their pathogenicity has not yet been investigated. Here, we isolated and evaluate two novel genotypes of A(H5N6) subtype in Mongolia during 2018–2019 (A/wildDuck/MN/H5N6/2018-19). Their evolution pattern and molecular characteristics were evaluated using gene sequencing and their pathogenicity was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The pathogenicity of HB1905 in mice was consistent with studies of swan-origin H5N6 AIV isolated in 2020 and H5N6 AIV isolated from wild duck feces in 2022 [ 6 , 17 ]. The pathogenicity of the HB1907 virus in mice was significantly higher than that of the HB1905 virus.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The pathogenicity of HB1905 in mice was consistent with studies of swan-origin H5N6 AIV isolated in 2020 and H5N6 AIV isolated from wild duck feces in 2022 [ 6 , 17 ]. The pathogenicity of the HB1907 virus in mice was significantly higher than that of the HB1905 virus.…”
Section: Discussionsupporting
confidence: 81%
“…Phylogenetic analysis of HA genes showed that the two H5N6 strains isolated in this study belong to the clade 2.3.4.4h H5N6 AIVs, which is consistent with the clade of H5N6 strains prevailing in China during 2018–2020 reported in previous studies [ 39 ]. At the same time, the HA proteins of the two strains in this study had multiple basic amino acids at the cleavage site (RERRRKR↓G), which is a characteristic of HPAIV [ 17 , 39 , 40 ]. These indicated that the viruses were capable of causing high death rates in poultry [ 6 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te human mortality rate with H5Nx viruses is higher than that with other infuenza subtypes, including seasonal infuenza viruses [61]. Te evolving H5Nx viruses are becoming increasingly virulent in mammalian models [1,62,63]. Specifcally, the HAs of the H5N1 and H5N6 subtypes isolated after 2020 in the subclades 2.3.4.4b and 2.3.4.4h showed an afnity for both α2,3 and α2,6 SA receptors and high replication capacity in mice [1,64].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we aimed to develop a rapid fluorescent diagnostic system for early detection of the H5 HPAIVs subclade 2.3.4.4, one of the most emerging variant subclades of the H5 HPAIVs lineage, in order to distinguish it from other H5 LPAIVs in chicken feces [ 23 , 24 ]. The E. coli host was replaced by reverse genetics of influenza viruses based on a mammalian expression system to develop H5Nx 2.3.4.4-specific mAbs, which were combined with a fluorescence material and suitable lysis buffer to discriminate between H5 HPAIVs and H5 LPAIVs.…”
Section: Introductionmentioning
confidence: 99%